Growth Performance of Different Tree Species in Agroforestry Systems in IGNP Command Area in Western Rajasthan - Singh, Bilas; Dhana Ram; Om Prakash; Deepak Kumar; Bhawana Sharma; Mana Ram Baloch (Annals of Arid Zone, 2024)
Tree integration in agriculture lands is climate resilient land use system traditionally practiced for improved productivity in arid regions. It enhances land productivity and improves livelihoods of rural dwellers. Four agroforestry models that includes block plantations of Prosopis cineraria (Khejri), Tecomella undulata (Rohida), grafted Zizyphus mauritiana (Ber) and Cordia myxa (Gunda) and boundary plantations of Dalbergia sissoo (Shisham), Carissa carandas (Karonda) and Cordia myxa were assessed at two sites within 500 m distance involving two farmers. Seedlings were planted in September 2021. Different crops were cultivated during kharif and rabi seasons of 2021 and 2022. Plants were measured for height and collar diameter and crop yields recorded. After two years of establishment, P. cineraria and T. undulata seedlings exhibited 99.0% survival, whereas seedlings of Z. mauritiana and C. myxa showed survival of 93.0% and 95.0%, respectively. Survival was relatively greater under block plantation as compared to the boundary plantations. Height and collar diameter growth of T. undulata was greater (p